2008
DOI: 10.4103/0973-1482.43140
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation between re-irradiation and demand endoscopic dilatation vs endoscopic dilatation alone in patients with recurrent/reactivated residual in-field esophageal malignancies

Abstract: A trial of re-irradiation with external beam is justified in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Concerning the potentially serious complications, re-RT was performed in a small and highly selected group of patients in clinical practice. In a prospective and randomized study, which included 34 patients who received re-RT and 35 patients who received dilatation alone, 6 cases of TEF were observed in the non-re-RT group, while no case of TEF was found in the re-RT group [ 21 ]. In the current study, no statistical differences were found in the incidence of TEF ( P = 0.613) and pericardial/pleural effusion ( P = 0.197) between re-RT and non-re-RT groups.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the potentially serious complications, re-RT was performed in a small and highly selected group of patients in clinical practice. In a prospective and randomized study, which included 34 patients who received re-RT and 35 patients who received dilatation alone, 6 cases of TEF were observed in the non-re-RT group, while no case of TEF was found in the re-RT group [ 21 ]. In the current study, no statistical differences were found in the incidence of TEF ( P = 0.613) and pericardial/pleural effusion ( P = 0.197) between re-RT and non-re-RT groups.…”
Section: Discussionmentioning
confidence: 99%
“…Teli et al [13] reported a prospective and randomized study that included 34 patients who were palliated with re-RT and 35 patients who refused re-RT and received peroral demand dilatation alone. Patients in the re-RT group showed better and more sustained improvement in their grade of dysphagia.…”
Section: Discussionmentioning
confidence: 99%